PENGARUH KEADILAN ORGANISASI TERHADAP KOMITMEN AFEKTIF MELALUI KEPUASAN KERJA PADA PERUSAHAAN PERBANKAN SWASTA DI DKI JAKARTA - Darra Pradita Hidayat (Jurnal Manajemen dan Pemasaran Jasa, 2015)
This research refers to a previous study conducted by Matthew S. Crow, Chang-Bae Lee Jae-Jin and Joo (2011) and completed by Andy Myhill & Ben Bradford (2012). This research is about “The Impact of Organizational Justice to Affective Commitment mediated by Job Satisfaction on Banking Companies In Jakarta”. The background of this research is to analyze the Affective Commitment as determining factors dedication and loyalty in banking industry. The purpose of this research was to examine the impact of Organizational Justice to Affective Commitment mediated by Job Satisfaction. The design of this research using primary data obtained by distributing questionnaires to 130 employees of Private Bank in Jakarta. Data analysis method used in this research is Structural Equation Model (SEM). The results of this research concluded that there is a positive effect of Organizational Justice, Procedural Justice, Distributive Justice, Interactional Justice against Affective Commitment through Job Satisfaction.